Looking inside an EFL classroom: Promoting productive learning through teachers’ questioning strategies - Teuku Zulfikar; Khairiah Syahabuddin; Khamisna Maulidia; Emawati Emawati; Amiruddin Amiruddin (Studies in English Language and Education, 2022)
Engaging students to participate in productive learning is a prerequisite for successful instruction. Teachers as instructional leaders should be creative and proactive in finding the best ways to enable effective learning to take place. One of the most well-known strategies is the use of appropriate ‘questioning’ during the instructional process. Teachers’ questioning strategies can encourage learning, but at the same time, they can also discourage learning when they are not carried out effectively. As teachers’ ways of posing questions are paramount for effective learning, it is timely to research this issue, teachers’ ways of asking questions during classroom instruction, and their students’ responses. The participants were two English teachers and their students at a secondary school in Aceh Province, Indonesia. The data were collected through classroom observations, in-depth interviews, and questionnaires. The study found that teachers used various questioning strategies, such as designing icebreaking activities and giving simple quizzes as attention grabbers. In addition, some types of questioning strategies, such as repetition, simplification, decomposition, structuring the questions, reacting to the students’ answers (giving a reward, complimenting, and motivating the students), using native language, and giving students some wait time to think about the answers were among the many strategies applied in the classroom. These questioning strategies were considered effective by the teachers and students in the study to promote productive language learning.